Severe hematologic toxicity after low-dose methotrexate in ectopic pregnancy: role of MTHFR polymorphism and drug interaction - a case report and literature review - Huang, Xiaojie; He, Fangjie; Deng, Yanhong; Shi, Shengying (Frontiers in Pharmacology, 2025)
BackgroundLow-dose methotrexate (MTX) is a standard treatment for ectopic pregnancy. While generally safe, it can rarely cause life-threatening hematologic toxicity. The mechanisms underlying these severe reactions in patients without traditional risk factors are poorly understood. We report a case of severe pancytopenia and systematically analyze the literature to characterize this rare but critical complication in MTX treatment for ectopic pregnancy.Case PresentationA 24-year-old woman received a single 50 mg/m2 dose of MTX for a persistent ectopic pregnancy while on concurrent benzathine penicillin therapy for syphilis. Within 24 h, she developed nausea, vomiting, and facial edema, rapidly progressing to severe mucositis and life-threatening pancytopenia with absolute neutrophil count nadir of 0.1 × 109/L, platelet nadir of 8 × 109/L and hemoglobin nadir of 76 g/L. Investigations revealed delayed MTX clearance and a heterozygous methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, a known genetic risk factor for MTX toxicity. A diagnosis of MTX toxicity was made, and she fully recovered after intensive supportive care including hydration, urine alkalinization, calcium leucovorin rescue, hematopoietic growth factors, and antibiotics.ConclusionSevere MTX toxicity following low-dose treatment for ectopic pregnancy is a rare but potentially fatal complication, with 3 deaths among 16 reviewed cases. Our analysis suggests a multifactorial etiology involving genetic predisposition and pharmacokinetic interactions. The MTHFR C677T variant compromises folate metabolism, while concurrent medications like benzathine penicillin may impair MTX renal clearance through competitive inhibition of organic anion transporters. Early symptom onset precedes standard monitoring schedules, necessitating enhanced clinical vigilance and consideration of pharmacogenetic factors and drug interactions in clinical practice.